(untitled) (Research, Society and Development, 2020)
The objective of the work was to evaluate the composition of the soil seed bank of three phytophysiognomy of the Cerrado Biome seeking to answer the following hypotheses: (1) the diversity of the soil seed bank reflects the diversity of the native phytophysiognomy to which it is inserted; (2) the soil seed bank of these phytophysiognomies has the potential to restore degraded areas. To evaluate statistically the soil seed bank, a completely randomized design (CRD) was used with four treatments and thirty repetitions (4 x 30): T1- control (washed and autoclaved sand); T2- seed bank of Cerrado Stricto sensu (CS) soil; T3-seed bank of Cerradão soil (CD); T4- seed bank of the soil of Mata de Galeria (MG). The soil seed bank represented 1,240 individuals, distributed in the three areas. In this study, the hypothesis that the diversity of the soil seed bank is a reflection of the vegetation to which it is inserted is rejected, being evident a dissimilarity of the soil seed bank between the three evaluated areas. It is suggested that these differences found in the floristic diversity of the soil seed bank may be influenced by the anthropogenic disturbances of adjacent areas and by the edaphoclimatic characteristics such as soil type, humidity and relief. The second hypothesis can be met if the soil seed bank is used to provide a quick covering of the soil, however, it must be combined with enrichment of native zoochoric species characteristic of the vegetation to be recovered.